1983
DOI: 10.1152/ajpendo.1983.244.6.e528
|View full text |Cite
|
Sign up to set email alerts
|

Defective sarcoplasmic reticular calcium transport in diabetic cardiomyopathy

Abstract: The effects of insulin and thyroid hormone treatments on cardiac sarcoplasmic reticular function were investigated in chronic streptozotocin-induced diabetes in rats. ATP-dependent Ca2+ transport and Ca2+-stimulated ATPase activities were depressed significantly in microsomal samples from diabetic rats in comparison with control (P less than 0.05). This defect was seen at various times of incubation (1-20 min) and different concentrations of free Ca2+ (10(-7) to 10(-5) M Ca2+) and was accompanied by changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
137
0
2

Year Published

1990
1990
2005
2005

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(148 citation statements)
references
References 26 publications
9
137
0
2
Order By: Relevance
“…7 Proposed mechanisms include reductions in either the density or the activity of 2 1 ATPase, 8 ' 9 ' 18 alterations in membrane Values represent mean±SD obtained 8 weeks after initiation of diabetes or treatment. P m maximum left ventricular developed pressure (LVDP); Tp, time to P ,^ T n time from P,^, to minimum LVDP; LV-dP/dt, maximum rate of left ventricular pressure decline; SHR, spontaneously hypertensive rats; T 3 , triiodothyronine; I, protamine zinc insulin; WKY, Wistar-Kyoto rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Proposed mechanisms include reductions in either the density or the activity of 2 1 ATPase, 8 ' 9 ' 18 alterations in membrane Values represent mean±SD obtained 8 weeks after initiation of diabetes or treatment. P m maximum left ventricular developed pressure (LVDP); Tp, time to P ,^ T n time from P,^, to minimum LVDP; LV-dP/dt, maximum rate of left ventricular pressure decline; SHR, spontaneously hypertensive rats; T 3 , triiodothyronine; I, protamine zinc insulin; WKY, Wistar-Kyoto rats.…”
Section: Discussionmentioning
confidence: 99%
“…lipid profiles, 8 -2829 and changes in the degree of membrane phosphorylation. 30 Until now, studies of this kind have been restricted to nonhypertensive, nonhypertrophic models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, the SR calcium content declines, leading to a reduced systolic calcium release and therefore a weaker cardiac contraction (9,10). At the molecular level, the impairment of SR function was shown to be caused by a reduced activity of the SR calcium pump (SERCA2a), which induced diastolic relaxation by sequestering calcium from the cytoplasm (11). SERCA2a activity depends on the amount of SERCA2a protein and is further regulated by its inhibitory protein phospholamban.…”
mentioning
confidence: 99%
“…1,2 Several defects have been proposed to explain the pathogenesis of diabetic cardiomyopathy, including a reduced adrenoreceptor myocardial density, alterations in contractile proteins, impaired calcium cellular movements, and defective energy metabolism. [1][2][3][4][5] Several anatomical and functional abnormalities of the microcirculation were recognized in the human diabetic heart without obstructive coronary atherosclerosis or coexisting arterial hypertension. 6 Moreover, it has been shown that DM is associated with both reduced coronary flow reserve [7][8][9] and impaired endothelial-dependent epicardial coronary vasodilation.…”
Section: Introductionmentioning
confidence: 99%